Dunia Ekonomi sebagai Mimbar Memuliakan Allah: Diskursus Teologi John Calvin - Verliany Riasty Vindy Manunay (Program Pascasarjana UKIM, 2022)
This article aims to conduct a discourse on the theological thought of John Calvin, a church reformer, regarding the unity of theology and economics. Calvin's post-reformation theological view understands the world as a theater to glorify God. Economic development, one of the essential parts of the world, could lay the foundation for church missions. This idea is essential in equipping the church to encourage economic growth and empower people. However, the reformed churches, especially those with the Calvinist wing, still view the world in a dichotomous way. The separation between the physical and spiritual worlds, the sacred and the profane, makes the church's theological doctrine about the economy and empowering people to tend to be misunderstood. This study uses a qualitative approach, which is based on the exploration of John Calvin's theological arguments regarding economic development. In the end, this research confirms that Calvin's theological thinking about economics as a theater to glorify God needs to become an operative theology that urges the church to care about economic development and empowering people.